Increasing incidence of recent hepatitis C virus infection among persons seeking voluntary counselling and testing for HIV and sexually transmitted infections in Taiwan. Issue 10 (13th October 2015) - Tsai, Jen-Chih; Hung, Chien-Ching; Chang, Sui-Yuan; Liu, Wen-Chun; Wu, Cheng-Hsin; Su, Yi-Ching; Wu, Pei-Ying; Luo, Yu-Zhen; Chang, Lan-Hsin; Sun, Hsin-Yun; Chang, Shan-Chwen
Abstract : Objectives: The incidence of hepatitis C virus (HCV) infection among HIV-negative men who have sex with men (MSM) is rarely investigated in the Asia-Pacific region. We aimed to estimate the incidence rate of and factors associated with recent HCV infection among the clients seeking voluntary counselling and testing (VCT) services for HIV in Taiwan. Methods: During 2006–2013, 12 143 clients sought VCT services for HIV. Clients with subsequent follow-up tests at an interval of 6 months or longer were included to estimate the incidence rate of HCV seroconversion. Phylogenetic analysis of HCV sequences from VCT clients and HIV-positive patients was performed. Results: The overall HCV seroprevalence at baseline was 0.3%. Of 2150 clients testing negative for anti-HCV antibody at baseline with a total of 5074.99 person-years of follow-up (PYFU), 17 (0.8%) developed HCV seroconversion, leading to an overall incidence rate of 3.35 per 1000 PYFU (95% CI 1.76 to 4.94), which increased from 2.28 (95% CI 0.05 to 4.51) in 2006–2009, to 3.33 (95% CI 0.86 to 5.80) in 2010 to 2011 and 4.94 per 1000 PYFU (95% CI 0.99 to 8.99) in 2012–2013; the incidence of early syphilis increased from 11.91 to 13.28 and 31.78 per 1000 PYFU in the three corresponding periods. In multivariate analysis, having HIV-positive partners (adjusted HR (AHR) =3.756; 95%CI 1.180 to 11.955) and developing a rapid plasma reagin titre of 4 or greater (AHR=9.978; 95% CI 1.550 to 64.233) were significantly associated with HCV seroconversion. Conclusions: An increasing trend of recent HCV infection occurs among individuals seeking VCT services in Taiwan. Having HIV-positive partners and having syphilis are independently associated with recent HCV seroconversion.